Field-Oriented Control of the PMSM with 2-DOF PI Controller Tuned by Using PSO - Celik, Hakan; Yigit, Tevfik (Ieee, 2018)
Nowadays, Permanent Magnet Synchronous Motors (PMSM) are used extensively in direct drive systems. In this study, Field-Oriented Control (FOC) of PMSM was performed with 2-DOF PI controller. Field-oriented control of the PMSM was modelled in the MATLAB / Simulink environment and the simulated results for both the traditional PI controller and the 2-DOF PI controller were compared. The parameters of 2-DOF PI and the traditional PI controllers, used in the study was determined by Particle Swarm Optimization (PSO). When the obtained simulated results are examined, it is seen that the 2-DOF PI controller has better performance than the traditional PI controller in FOC of the PMSM.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: PMSM; Field-Oriented Control; 2-DOF PI Controller; PSO